Academic Performance and its Relation with Intrinsic Factors in Engineering Students (2018)
The association between academic performance, self-regulation, psychological well-being and cognitive processes was studied in 950 students of the engineering programs of the University of Cartagena between 2014 and 2016. The academic performance was eval